Break-even analysis - Goh, Yah Huay (2015)
Break-even analysis is basically concerned with the exact ascertainment of profit thresholds (the break-even points), the requisite data preparation and further related analysis. In the pursuit of this concept, this report addresses the issues of break-even analysis in practical applications. The research methodology adopted involves performing a literature review of books and journals regarding the current issues and applications of break-even analysis. To illustrate the practical aspects, three companies which practice break-even analysis are studied and presented as cases in the report. Through interviews with the key management personnel, the data gathered were then analyzed to address the issues in break-even implementation. The scope includes a profile of the companies, their break-even approaches, the assumptions used in the break-even computations and the problems that were encountered during implementation. The results obtained revealed that the break-even model has extensive uses in these companies. However, due to the fact that the assumptions are rather stringent, the break-even analyses adopted by the companies are rather simplified. As such, other techniques are used to supplement the break-even model.